(untitled) (Eurasian Journal of Engineering and Technology, 2022)
This article presents a theoretical and experimental study of a micro-hydro power plant that effectively operates in low-pressure watercourses with a water flow speed of 1-4 m/s. According to the results of the study, it was found that a 1.5 kW micro-hydro power plant installed on the Kuymazar canal flowing on the territory of the «Bukhoro Chorvo Omad» farm located in the Bukhara region at a water flow speed of 4 m/s is capable of generating 12,000 kWh of electricity per year. Due to the introduction of the developed micro-hydro power plant on a farm, about 9,834 toe were saved and more than 14.64 tons of carbon dioxide (CO2) were prevented from being released into the atmosphere.